Science Fiction Prototyping: Flexible Settings in Immersive Environments - Pirker, J.; Weghofer, P.; Guetl, Christian (International Association of Online Engineering, 2013)
This paper presents an in-depth analysis of the importance of innovative Science Fiction Prototyping systems in different sectors with focus on educational aspects and the support of virtual environments. Therefor we investigate the utility of Science Fiction Prototypes in different environments and introduce a design model to implement flexible setups in virtual world. We illustrate how configurable Science Fiction Prototypes can be designed and implemented in virtual world environments by introducing a first example in Open wonderland. We close by explicating the prospect of such flexible setups and discuss briefly the impact in learning and training scenarios.